A 5-year review of pattern of placenta previa in Ilorin, Nigeria - Omokanye, L.O.; Olatinwo, A.W.O.; Salaudeen, A.G.; Ajiboye, A.D.; Durowade, K.A. (International Journal of Health Sciences, 2017)
Background: Placenta previa, a major cause of obstetric hemorrhage, is potentially life-threatening to the mother and frequently results in high perinatal morbidity and mortality. Methodology: This is a retrospective study of all cases of placenta previa managed at the University of Ilorin Teaching Hospital over a 5-year from January 2011 to December 2015. A pro forma template was used to harvest information from case notes of patients involved in the study. Results: There were a total of 10,250 deliveries over the 5-year study and 164 cases of placenta previa were managed during this period; giving an incidence of 1.6% of the total deliveries. Of these patients, 65.9% were unbooked while 34.1% were booked. 110 (67%) were above 30 years of age and 51.2% were grand multiparous women. The majority (81.7%) of the patients belonged to the low socioeconomic class. Painless vaginal bleeding (62.2%), intrapartum hemorrhage (22.6%), and abnormal lie presentation (8.5%) were the most common mode of presentation. Vaginal delivery occurred in (29.3%) of patients while 70. 7% were delivered through cesarean section. There was a signifi cant association between patients’ age, parity, booking status, and types of placenta previa (P < 0.05). Similarly, there was a significant association between gestational age at delivery, mode of delivery, intraoperative blood loss, and birth weight at delivery and types of placenta previa (P < 0.05). Perinatal mortality was 12.2%, 15.6% of babies had severe birth asphyxia, and there was no maternal mortality. Conclusion: From this study, the risk factors for placenta previa are advanced maternal age above 35 years, grand multiparity, and booking status. Early recognition, appropriate referral of these patients and availability of ultrasound facilities, blood transfusion facilities, improvement in neonatal facilities and trained personnel will go a long way in reducing the perinatal mortality from placenta previa.